Magnetron sputter deposition of silver onto castor oil: The effect of plasma parameters on nanoparticle properties - Sergievskaya, Anastasiya; O’Reilly, Amy; Chauvin, Adrien; Veselý, Jozef; Panepinto, Adriano; De Winter, Julien; Cornil, David; Cornil, Jérôme; Konstantinidis, Stéphanos (Colloids and surfaces. A, Physicochemical and engineering aspects, 2021)
[Display omitted] Magnetron sputter deposition of metals onto low vapor pressure liquids is a clean and straightforward method of nanoparticle (NP) production. Herein, we discuss the production of silver nanoparticles (Ag NPs) via magnetron sputtering of a silver target onto castor oil, a biocompatible and highly available liquid. A state-of-the-Art (bipolar) high-power impulse magnetron sputtering (HiPIMS) was used for the first time for the sputtering onto liquid procedure. The effect of several parameters such as sputter time, applied power, working gas pressure, and type of sputtering plasma (direct current magnetron sputtering (DC-MS) vs. HiPIMS and bipolar HiPIMS) onto NP properties has been studied by UV–vis spectroscopy and transmission electron microscopy (TEM). The scenario of Ag NPs formation is inferred from these analyses, and further supported by mass-spectrometry and quantum-chemistry calculations. Initial Ag NPs formed in castor oil have a diameter ranging from 0.8 nm to 4 nm, its stability is discussed in terms of the plasma-liquid surface interaction and the quantum chemistry data.